The Unstoppable Rise of the Importance Given to Quantity - Al, Umut (Information World, 2023)
This paper intends to serve multiple purposes. Although the paper is mainly a review of the book titled Provincial Universities: AK Party’s Back Campus, it aims to make a small contribution to the relevant parties to seriously consider the different dimensions of the problematics of quality vs quantity. On the other hand, the intention to show that book reviews are not just a type of publication in which the contents of the books are conveyed to the reader has led to the emergence of this text. In this context, creating a course material on book reviews for the course called Scholarly Communication, which it has been taught at undergraduate and graduate levels for many years, is among the motivations of the paper. The selection of Information World as the publication journal should be accepted as part of the intention to present the general outlook of the book reviews in this journal, and to show potentially relevant parties how the university and research phenomena have been undermined over time. In the paper, the parts related to university libraries are also shared within the framework of the book contents.